2017
DOI: 10.1371/journal.pone.0177705
|View full text |Cite
|
Sign up to set email alerts
|

Within-session decrement of the emission of licking bursts following reward devaluation in rats licking for sucrose

Abstract: We previously observed that dopamine D2-like receptor blockade in rats licking for sucrose produced a within-session decrement of the emission of licking bursts similar to the effect of either reward devaluation, or neuroleptics, on operant responding for different rewards, which, accordingly, we interpreted as an extinction-like effect. This implies that exposing animals to reward devaluation would result in a drop of burst number taking place only after the contact with the devalued reward. To test this pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 40 publications
5
20
0
Order By: Relevance
“…To do so, we analyzed the licking microstructures during the consumption of the freely accessible reward, which allows assessing several components of consummatory behavior, such as basal hunger, postingestive negative feedback, and palatability of the ingested tastant (Figure A). The number of licks per burst ( t [40] = 0.20; P = 0.842) (Figure F), burst duration ( t [40] = 1.382; P = 0.175) (Figure G), interlick interval ( t [40] = 0.944; P = 0.351) (Figure H), and lick frequency in bursts ( t [40] = 0.234; P = 0.817) (Figure I) were identical in both groups, suggesting similar hedonic reactivity to the reward.…”
Section: Resultsmentioning
confidence: 99%
“…To do so, we analyzed the licking microstructures during the consumption of the freely accessible reward, which allows assessing several components of consummatory behavior, such as basal hunger, postingestive negative feedback, and palatability of the ingested tastant (Figure A). The number of licks per burst ( t [40] = 0.20; P = 0.842) (Figure F), burst duration ( t [40] = 1.382; P = 0.175) (Figure G), interlick interval ( t [40] = 0.944; P = 0.351) (Figure H), and lick frequency in bursts ( t [40] = 0.234; P = 0.817) (Figure I) were identical in both groups, suggesting similar hedonic reactivity to the reward.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of licking microstructure, including the numbers of total licks, which indicate the extent of feeding activity, is commonly used to evaluate changes in fluid ingestion and thus general drinking behaviour (D'Aquila et al., ; Davis, ; Higgs & Cooper, ; Mendez, Maidment, & Murphy, ). Rodents typically cluster their licks into separate sets known as bursts or bouts (D'Aquila & Galistu, ; Johnson, ). The number of bursts reflects the incentive motivation triggered by cues because it indicates the activation of responses (Johnson, Sherwood, Smith, Gallagher, & Holland, ; Johnson et al., ; Smith, ).…”
Section: Discussionmentioning
confidence: 99%
“…The mesolimbic dopamine (DA) system is involved in reward‐oriented behaviours (Berridge, ; Flagel & Robinson, ), and DA antagonism in rodents changes their ingestive behaviours (Galistu & D'Aquila, ; Robles & Johnson, ; Salamone, Correa, Yang, Rotolo, & Presby, ). The licking behaviour of rodents is widely used as a means to explore how liking (hedonic impact of reward), wanting (incentive motivation), and learning (reward prediction) modulate animal behaviours (Berridge, ; Berridge, Robinson, & Aldridge, ; D'Aquila & Galistu, ; Dastugue, Merlin, Maquart, Bernard, & Besnard, ; Davies et al., ; Johnson, ; Taha & Fields, ; Uematsu et al., ). Pharmacology studies showed that dopaminergic (DAergic) stimulation of the nucleus accumbens (NAc) triggers an intense response to obtain a reward, even if a rat has undergone extinction training (Peciña & Berridge, ; Saunders & Robinson, ; Singer et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Repeated exposure to sucrose reward—which depends both on taste and on caloric content—can induce neuroadaptations leading to the release of eating behaviour from the control of homeostatic mechanisms, thus resulting in compulsive overeating [ 14 ]. The analysis of the licking microstructure reveals specific responses to taste or hunger/satiety internal cues [ 15 20 ], which are related to the process by which reward evaluation regulates behavioural activation [ 15 , 21 25 ]. In more detail, the number of lick bursts—i.e.…”
Section: Introductionmentioning
confidence: 99%